Entomologia - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
Losses in root and planting material production caused by different pests as well as their biological control are evaluated. Studies of pests damaging dried cassava in storage were initiated. Biological aspects and form of attack of the following pests are described: stemborers (Lagochirus rogersi, L. araneiformis, Chilomina clarkei), shoot flies (Silba pendula), nymphs and adults of Cyrtomenus bergi, and lacebugs (Vatiga manihotae and V. illudens). Zelus nugax (Reduviidae) was identified as a major predator of V. manihotae. The presence of whiteflies (Aleurotrachelus socialis) and sooty mold reduces root yield. The varietal preference for oviposition by Erinnyis ello was determined as well as the effect of simulated damage on yield, starch content, and cooking quality of cassava. Five major enemies of the cassava mealybug Phenacoccus herreni were identified: Ocyptamus, Cleothera, Anagyrus, Sympherobius, and Chrysopa. An unidentified species of mite belonging to the family Eriophyidae found attacking cassava leaves is parasitized by the fungus Hirsuthella tompsonii. Fifteen insect species were found feeding on stored cassava; among these,Araecerus fasciculatus and Lasioderma serricorne are the most frequently found pests. Both species are parasitized by the hymenopteran Anisopteromalus sp. (CIAT)